Carbohydrates and thermal properties indicate a decrease in stable aggregate carbon following forest colonization of mountain grassland - Guidi, Claudia; Cannella, David; Leifeld, Jens; Rodeghiero, Mirco; Magid, Jakob; Gianelle, Damiano; Vesterdal, Lars (Soil Biology and Biochemistry, 2015)
In mountainous areas of Europe, the abandonment of grasslands followed by forest expansion is the dominant land-use change. Labile (i.e. easily decomposable) litter represents the major source for soil microbial products, which promote soil aggregation and long-term C stabilization. Our objective was to investigate changes in the content and origin of soil C components involved into aggregate stabilization (i.e. carbohydrates) following forest expansion on abandoned grassland in the Alps, where only few studies have been conducted.